Modelos probabilísticos discretos - Souza, Washington Luiz Martins de (2020)
Today's society needs and requires more and more people capable to understand math as we are constantly faced with numbers, formulas, graphs and other mathematical content. These subjects are important and necessary for a student?s social life. We seek in this work to provide a brief history of probability, its basic principles, some insights on probabilistic models and examples on how to apply it in high school. In this sense, we aim to bring a didactic pedagogical approach for probability teaching that allows the student to think, present and create strategies for solving a problem. The student becomes a knowledge builder and the teacher acts as knowledge moderator that will explain, stimulate and supervise, without imposing mathematical truths that can often be obscured in the students' reality.